1996
DOI: 10.1046/j.1365-2265.1996.737558.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐clinical Cushing's syndrome: an unexpected frequent cause of poor glycaemic control in obese diabetic patients

Abstract: The prevalence of pre-clinical Cushing's syndrome in obese patients with poorly controlled diabetes appears to be considerably higher than previously believed. The overnight dexamethasone suppression test proved to be a simple, sensitive and highly specific screening test for Cushing's syndrome despite the presence of obesity and hyperglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
6
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(133 citation statements)
references
References 24 publications
(30 reference statements)
3
108
6
10
Order By: Relevance
“…It is not uncommon that Cushing's syndrome is diagnosed only in advanced disease states several years after the onset of symptoms, and so the disease is typically associated with substantial morbidity and mortality (1,2). Mild forms of Cushing's syndrome, however, probably often remain undiagnosed in obese diabetic patients (3,4). Therefore, reliable and convenient screening tests for Cushing's disease are of particular clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon that Cushing's syndrome is diagnosed only in advanced disease states several years after the onset of symptoms, and so the disease is typically associated with substantial morbidity and mortality (1,2). Mild forms of Cushing's syndrome, however, probably often remain undiagnosed in obese diabetic patients (3,4). Therefore, reliable and convenient screening tests for Cushing's disease are of particular clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic Cushing's syndrome may be an unsuspected finding in patients with type 2 diabetes mellitus with a prevalence as high as 3% (43,44,45,46,47). The converse is also true in that patients with diabetes mellitus with poor glycemic control may have an activated HPA axis (48).…”
Section: Type 2 Diabetes Insulin Resistance and The Metabolic Syndromementioning
confidence: 92%
“…Leibowitz et al [13] reported three patients with sub-CS in a study of 90 overweight patients (body mass index > 25 kg/m 2 ) with poorly controlled diabetes (HbA1c > 9%). Catargi et al [14] reported three patients with subCD and one patient with subCS in a group of 200 overweight patients (body mass index > 25 kg/m 2 ) with poorly controlled diabetes (HbA1c > 8%).…”
Section: Characteristics Of Suspected Subcd Patientsmentioning
confidence: 99%